Immediate or delayed initiation of renal replacement therapy in patients with leptospirosis and acute kidney injury: a target trial emulation - Marie Julien; Cédric Rafat; Loïc Raffray; Henri Vacher-Coponat; Nicolas Allou; Jérôme Allyn; Julien Jabot; Yannis Lombardi (Annals of Intensive Care)
Abstract Background Anecdotal evidence suggests that early renal replacement therapy (RRT) may improve the mortality associated with acute kidney injury (AKI) in patients with leptospirosis. Conversely, several randomized controlled trials (RCTs) conducted in intensive care units have refuted the positive impact of early RRT on mortality in patients with AKI and other causes of sepsis. Methods In this emulated RCT utilizing a propensity score-weighted logistic regression performed in the two academic centers on the island of La Réunion, France, between 2010 and 2020, we evaluated the impact of the timing of RRT on a composite outcome of mortality or new-onset or worsening chronic kidney disease (CKD) within a year, in patients hospitalized with leptospirosis, Stage 3 AKI, and no immediate need for RRT. Results We included 295 consecutive patients with leptospirosis and Stage 3 AKI: 82 (28%) began RRT within 48 h of admission (“early” group), 213 (72%) did not start RRT within 48 h (“delayed” group). In the delayed group, 53/213 (25%) patients eventually required RRT. 59/295 patients (20%) met the primary outcome: 32 (15%) in the delayed group and 27 (33%) in the early group. The odds ratio (OR) for primary outcome occurrence before weighing was 2.78 (95% confidence interval CI 1.53 to 5.01, p < 0.001; reference: delayed group) and after weighting was 2.08 (95% CI: 1.01 to 4.26, p = 0.046). In secondary analyses, there was a significantly higher probability of CKD occurrence in the early group (OR 2.74, 95% CI 1.25 to 6.0, p = 0.012). Mortality at 1 year did not differ between groups (OR 0.76, 95% CI 0.21 to 2.68, p = 0.666). Conclusion Early initiation of RRT may be associated with an increased risk of death and development of CKD within 1 year in patients with leptospirosis and Stage 3 AKI.